2017
DOI: 10.1002/bit.26508
|View full text |Cite
|
Sign up to set email alerts
|

Production of itaconic acid from acetate by engineering acid‐tolerant Escherichia coli W

Abstract: Utilization of abundant and cheap carbon sources can effectively reduce the production cost and enhance the economic feasibility. Acetate is a promising carbon source to achieve cost-effective microbial processes. In this study, we engineered an Escherichia coli strain to produce itaconic acid from acetate. As acetate is known to inhibit cell growth, we initially screened for a strain with a high tolerance to 10 g/L of acetate in the medium, and the W strain was selected as the host. Subsequently, the WC strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(141 citation statements)
references
References 47 publications
3
137
1
Order By: Relevance
“…3). Although they share similar (Zhang et al 2008) atpA P. acidipropionici Propionic acid (Guan et al 2014) CgAMD1 C. glabrata Hydrochloric acid (Wu et al 2018) Decarboxylation and deamination cad E. coli Acetic acid (Noh et al 2018) ybaS, gadC E. coli Hydrochloric acid (Lu et al 2013) hdcAPB L. lactis Hydrochloric acid (Trip et al 2012) arcA, arcC, gdh, gadB, ybaS P. acidipropionici Propionic acid (Guan et al 2016) Cell resistance mechanisms, different species utilize a variety of specific elements as a response to acid stress. Therefore, customized strategies must be proposed for different strains.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…3). Although they share similar (Zhang et al 2008) atpA P. acidipropionici Propionic acid (Guan et al 2014) CgAMD1 C. glabrata Hydrochloric acid (Wu et al 2018) Decarboxylation and deamination cad E. coli Acetic acid (Noh et al 2018) ybaS, gadC E. coli Hydrochloric acid (Lu et al 2013) hdcAPB L. lactis Hydrochloric acid (Trip et al 2012) arcA, arcC, gdh, gadB, ybaS P. acidipropionici Propionic acid (Guan et al 2016) Cell resistance mechanisms, different species utilize a variety of specific elements as a response to acid stress. Therefore, customized strategies must be proposed for different strains.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…These results suggested that enhancing rhamnolipids production by mutagenesis was a promising strategy to realize low-foaming rhamnolipids fermentation under weakly acid conditions. In addition, other methods for strain improvement like metabolic engineering and synthetic biology techniques [37,38] should be included in future studies for improving rhamnolipids productivity under weakly acid conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we tried to deregulate the expression of metH using synthetic constitutive promoters (http:// parts.igem.org/Promoters/Catalog/Anderson) Noh et al, 2018Noh et al, , 2017. To restore the cell biomass, the metH expression needed to be increased than before as its insufficient expression produced less cell biomass.…”
Section: Optimization Of Meth Expression For Enhancing Coenzyme B 12 mentioning
confidence: 99%